Control temperature of the air conditioning system of a vessel from exergoeconomic analysis (2021)
In this work the air conditioning system of a 93 m long and 14 m wide vessel with 4081 refrigerated m3 distributed in 51 premises is studied. In which energy, exergetic and exergoeconomic analyzes were carried out for control temperatures between 20 and 27 ° C and 50% relative humidity, with outdoor air conditions of 35 ° C and 70% relative humidity. For the vessel, the thermal load is calculated with an adaptation of the ASHRAE CLDT / SCL / CLF (cooling load temperature difference/cooling load factor/solar cooling load factor) methodology and the ISO 7547 standard. Thermal load contributors taken into account for the study were heat transfer through walls, ceilings, and glass in addition to gains from people, lighting, and Appliances. Transmission through walls and ceilings represents 33% of the thermal load, followed by glass with 18% and power equipment with 15%, the last three sources of thermal load generation are Appliances (12%), people (12%) and lighting (10%). For each degree centigrade of the control temperature, the thermal load is reduced by 2.4 and 1.1%, respectively, as determined by the ASHRAE and ISO methodologies. Similarly, the destruction of exergy is reduced by 4.16% for each degree Celsius that the control temperature is increased. An indicator is proposed to calculate the cost of generation of cooling load per unit volume and exergy of the thermal load from which it is obtained that the higher the control temperature, the lower the value of the cost of generation of the cooling load. From the exergoeconomic analysis, it is highlighted that the destruction of exergy is the main factor in the increase in system costs. Increases in exergy destruction increase the value of the indicator of cooling load generation